Cystatin C: Its role in pathogenesis of OSMF - P.C. Anila Namboodiripad (Elsevier, 2014)
Oral Submucous Fibrosis (OSF) is a chronic disorder characterized by fibrosis of the mucosa lining the upper digestive tract involving the oral cavity, oro- and hypopharynx and the upper third of the oesophagus. The alkaloids from areca nut are the most important chemical constituents biologically, in producing this lesion. These chemicals appear to interfere with the molecular processes of deposition and/or degradation of extracellular matrix molecules such as collagen. Increased collagen synthesis or reduced collagen degradation have been considered as a possible mechanism in the development of the disease. Increased and continuous deposition of extracellular matrix may also take place as a result of disruption of the equilibrium between matrix metalloproteinases (MMPs) and tissue inhibitors of matrix metalloproteinases (TIMP). Arecoline a product of areca nut was found to elevate Cystatin C mRNA (CST3) and protein expression in a dose-dependent manner. Cystatin C expression was significantly higher in OSF specimens and expressed mainly by fibroblasts, endothelial cells, and inflammatory cells. Cross-links between the molecules are essential for the tensile strength of collagen fibres. These areas are resistant to attack by collagenases but can be attacked by a number of other serine and cysteine proteinases. CST3 encoding a cysteine proteinase inhibitor might contribute to the stabilization of collagen fibrils in OSMF. Treatment directed against Cystatin C may serve as a novel treatment for submucous fibrosis and also in preventing its transformation into malignancy.